Change in Plant-Based Diet Quality Is Associated with Changes in Plasma Adiposity-Associated Biomarker Concentrations in Women - Baden, Megu Y (J Nutr, 2019)
BACKGROUND: A healthful plant-based diet is associated with lower risk of cardiometabolic diseases. However, it is still unclear whether such benefits are due to its favorable effects on adiposity-associated biomarkers. OBJECTIVE: We investigated the associations between biomarkers and 3 plant-based diet indices: an overall plant-based diet index (PDI); a healthful plant-based diet index (hPDI); and an unhealthful plant-based diet index (uPDI). METHODS: In the Nurses’ Health Study II, 831 women [baseline mean age: 45 y; body mass index (BMI, kg/m(2)): 24.6] were randomly selected from those who provided 2 blood samples in 1996–1999 and 2010–2011 to measure plasma concentrations of adiponectin, leptin, soluble leptin receptor (sOB-R), insulin, retinol-binding protein-4, high-sensitivity C-reactive protein (hsCRP), and interleukin-6 (IL-6). Plant-based diet indices were derived from semiquantitative food frequency questionnaires assessed at each blood collection. Linear mixed models were used to evaluate cross-sectional associations, and general linear models were used to evaluate longitudinal associations. RESULTS: In cross-sectional analyses with multivariable adjustment including BMI, higher hPDI was associated with lower concentrations of leptin, insulin, and hsCRP, and higher adiponectin and sOB-R concentrations (biomarker differences per 10-point higher hPDI: −7.2%, −10.0%, −13.6%, 3.0%, and 1.9%, respectively; P ≤ 0.025). A higher uPDI was associated with higher concentrations of leptin and insulin (4.4% and 4.8%, respectively; P ≤ 0.048). In longitudinal analyses with multivariable adjustment including weight change, an increase in hPDI (improved plant-based diet quality) was inversely associated with changes in leptin and hsCRP (biomarker changes per 10-point hPDI increase: −7.7% and −17.8%, respectively; P ≤ 0.005), whereas an increase in uPDI (worsened plant-based diet quality) was positively associated with changes in leptin, hsCRP, and IL-6 (10.1%, 13.5%, and 12.4%, respectively; P ≤ 0.021). CONCLUSIONS: Adherence to a healthful plant-based diet is associated with favorable long-term changes in adiposity-associated biomarker concentrations in women.